Velocity observer-based event-triggered adaptive fuzzy attitude takeover control of spacecraft with quantized quaternion - Ning, Kai (2023)
In this article, the spacecraft attitude takeover control (ATC) problem with limited communication and the unavailable angular velocity using cellular satellites is addressed. First, a dynamic uniform quantizer (DUQ) is proposed to quantize unit quaternion between sensor cellular satellites and controller cellular satellite. Second, an adaptive fuzzy observer is proposed to estimate the unavailable angular velocity. Further, between controller cellular satellite and actuator cellular satellites, an event-triggered mechanism (ETM) is provided to lighten the communication burden. By combing DUQ, adaptive fuzzy observer, the adaptive fuzzy control law and the ETM is established. The stability of the ATC systems with the proposed control method is ensured. Finally, the simulation results illustrate the effectiveness of the developed control laws.